The strongly generalized double difference [chi] sequence spaces defined by a modulus - Subramanian, N; Misra, U.K (Scientia magna, 2012)
In this paper we introduce the strongly generalized difference [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII] where f is a modulus function and [A.sub.i] = [a.sup.i(mn).sub.i(k,l)] is a nonnegative four dimensional matrix of complex numbers and [p.sub.i(mn)] is a sequence of positive real numbers. We also give natural relationship between strongly generalized difference [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII]-summable sequences with respect to f. We examine some topological properties of [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII] spaces and investigate some inclusion relations between these spaces. Keywords De la Vallee-Poussin mean, difference sequence, gai sequence, analytic sequence, modulus function, double sequences. 2000 Mathematics subject classification: 40A05, 40C05, 40D05.